Simulation of Adult Surgical Cricothyrotomy for Anesthesiology and Emergency Medicine Residents: Adapted for COVID-19 - Mathieu Asselin; Alexandre Lafleur; Pascal Labrecque; Hélène Pellerin; Marie-Hélène Tremblay; Gilles Chiniara (Association of American Medical Colleges, 2021)
Introduction In a CICO (cannot intubate, cannot oxygenate) situation, anesthesiologists and acute care physicians must be able to perform an emergency surgical cricothyrotomy (front-of-neck airway procedure). CICOs are high-acuity situations with rare opportunities for safe practice. In COVID-19 airway management guidelines, bougie-assisted surgical cricothyrotomy is the recommended emergency strategy for CICO situations. Methods We designed a 4-hour procedural simulation workshop on surgical cricothyrotomy to train 16 medical residents. We provided prerequisite readings, a lecture, and a videotaped demonstration. Two clinical scenarios introduced deliberate practice on partial-task neck simulators and fresh human cadavers. We segmented an evidence-based procedure and asked participants to verbalize the five steps of the procedure on multiple occasions. Results Thirty-two residents who participated in the workshops were surveyed, with a 97% response rate (16 of 16 from anesthesiology, 15 of 16 from emergency medicine). Participants commented positively on the workshop's authenticity, its structure, the quality of the feedback provided, and its perceived impact on improving skills in surgical cricothyrotomy. We analyzed narrative comments related to three domains: preparation for the procedure, performing the procedure, and maintaining the skills. Participants highlighted the importance of performing the procedure many times and mentioned the representativeness of fresh cadavers. Discussion We developed a surgical cricothyrotomy simulation workshop for anesthesiology and emergency medicine residents. Residents in the two specialities uniformly appreciated its format and content. We identified common pitfalls when executing the procedure and provided practical tips and material to facilitate implementation, in particular to face the COVID-19 pandemic.